Honoring the voices of bereaved caregivers: a Metasummary of qualitative research - Holtslander, Lorraine (BMC Palliat Care, 2017)
BACKGROUND: Family caregiving in the context of advanced disease in particular, can be physically and emotionally taxing. Caregivers can subsequently face bereavement exhausted with few supports, limited resources and a significant proportion will develop negative psychological and social outcomes. Although some research has attended to the bereavement experiences of family caregivers who had cared for a person requiring palliative care, a comprehensive qualitative understanding of the impact of caregiving on bereavement has not been articulated. The purpose of this study was to conduct a qualitative metasummary to explore the experiences of bereaved family caregivers of people who received palliative care services, regardless of their underlying disease. METHODS: Sandelowski and Barroso’s qualitative metasummary method was utilized: 1287 articles were identified through extensive database searches (i.e. – MEDLINE, PsychINFO, and CINAHL) and reviewed to determine if they fit the criteria. Those included in the review were assessed for study quality. Findings from each study were then thematically coded and a frequency of themes was calculated. RESULTS: The sample consisted of 47 qualitative studies. A total of 15 themes emerged. In descending order of frequency, the 15 themes were: the individual emotions of serenity, sadness, guilt, uncertainty, trauma, escape, and anger; post-loss experiences that helped the caregiver in bereavement; post-loss experiences that hindered; practical life changes; caregiver role identity; pre-loss experiences that helped; pre-loss experiences that hindered; caregiver context; and a need for different kinds of supports. Three key findings emerged from the themes: (1) many different aspects of the caregiving experience impact the bereavement experience, (2) every bereavement experience is unique, and (3) a variety of supports must be developed and made available to caregivers to meet these unique needs. CONCLUSIONS: Based on the metasummary findings, changes are needed in practice and policy to ensure the health and well-being of the family caregiver is maintained by offering support both during caregiving and bereavement.